A linguagem da violência nos contos de Famílias terrivelmente felizes de Marçal Aquino - Mendes, Fábio Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The critical analysis of Famílias terrivelmente felizes (2003) short stories, by Marçal Aquino, aims at identifying the use that the author makes of a violence language that pervades the articulation of themes and motifs, the constitution of narrators, the characterization of characters, and the materiality of texts. In regard to content, this violence is adjusted, either predominantly or incidentally, to images of physical, psychological, social, and symbolical death, features of an authoritarian Brazilian society and raw material for the production line of a new realism present in contemporary Brazilian fiction. Therefore, the role of this language is ambiguous, thanks to the ironic happening, with its action marked by subtlety, but also being completely perverse, installing itself in the intimate life of irony interpreters that experience the emptying of public space in the Brazilian social and political post-military regime period. In these terms, national symbols related to family metaphor are questioned by Aquino’s short stories, such as to that represented by the supranational family, the Nation-state, and the one represented by the ideal model of bourgeois family

A análise crítica dos contos de Famílias terrivelmente felizes (2003), de Marçal Aquino, tem por objetivo identificar o uso que o autor faz de uma linguagem da violência que perpassa a articulação de temas e motivos, a constituição dos narradores, a caracterização das personagens e a materialidade dos textos. Quanto ao conteúdo, essa violência está ajustada às imagens da morte, seja de modo predominante ou incidental, física, psicológica, social e simbólica, traços de uma sociedade brasileira autoritária e matéria-prima da linha de produção do novo realismo que se faz presente na ficção brasileira contemporânea. Assim, a função dessa linguagem é ambígua, graças ao acontecimento irônico, sendo que sua ação é marcada pela sutileza, mas também totalmente perversa, se instalando na vida íntima dos intérpretes da ironia que experimentaram o esvaziamento do espaço público no período social e político brasileiro pós-regime militar. Nestes termos, símbolos nacionais relacionados à metáfora da família são questionados pelos contos de Aquino, tais como àquele representado pela família supra-nacional, o Estado-nação, e o representado pelo modelo ideal de família burguesa
Keywords: Aquino, Marçal 1958- Famílias terrivelmente felizes Crítica e interpretação; Literatura brasileira - História e crítica; Contos brasileiros - História e crítica; Violencia na literatura; Ironia na literatura; Hermeneutica; Brazilian literature History and criticism